Adjunct N-Acetylcysteine Treatment in Hospitalized Patients With HIV-Associated Tuberculosis Dampens the Oxidative Stress in Peripheral Blood: Results From the RIPENACTB Study Trial - Safe, Izabella P.; Amaral, Eduardo P.; Araújo-Pereira, Mariana; Lacerda, Marcus V. G.; Printes, Vitoria S.; Souza, Alexandra B.; Beraldi-Magalhães, Francisco; Monteiro, Wuelton M.; Sampaio, Vanderson S.; Barreto-Duarte, Beatriz; Andrade, Alice M. S.; Spener-Gomes, Renata; et al. (Frontiers in Immunology, 2021)
Tuberculosis (TB) still causes significant morbidity and mortality worldwide, especially in persons living with Human Immunodeficiency Virus (HIV). This disease is hallmarked by persistent oxidative stress and systemic inflammation. N-acetylcysteine (NAC), a glutathione (GSH) precursor, has been shown in experimental models to limit Mycobacterium tuberculosis infection and disease both by suppression of the host oxidative response and through direct antimicrobial activity. In a recent phase II randomized clinical trial (RIPENACTB study), use of NAC as adjunct therapy during the first two months of anti-TB treatment was safe. Whether adjunct NAC therapy of patients with TB-HIV coinfection in the context of anti-TB treatment could directly affect pro-oxidation and systemic inflammation has not been yet formally demonstrated. To test this hypothesis, we leveraged existing data and biospecimens from the RIPENACTB trial to measure a number of surrogate markers of oxidative stress and of immune activation in peripheral blood of the participants at pre-treatment and at the day 60 of anti-TB treatment. Upon initiation of therapy, we found that the group of patients undertaking NAC exhibited significant increase in GSH levels and in total antioxidant status while displaying substantial reduction in lipid peroxidation compared to the control group. Only small changes in plasma concentrations of cytokines were noted. Pharmacological improvement of the host antioxidant status appears to be a reasonable strategy to reduce TB-associated immunopathology.